2008
DOI: 10.1002/jmv.21338
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of rotavirus viremia in children with acute gastroenteritis: Discordance of strains detected in stool and sera

Abstract: Recently, rotavirus antigenemia and viremia have been identified in patients with acute gastroenteritis. This study examined rotavirus viremia in children hospitalized for acute gastroenteritis in order to establish its association with fecal shedding of rotavirus, infecting genotypes and antibody marker of acute infection. Thirty-one pairs of stool-serum specimens were collected from November 2004 to February 2005 together with clinical information. All paired specimens were screened for rotavirus RNA by RT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
13
2
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 30 publications
9
13
2
3
Order By: Relevance
“…Because this region of VP8 is spatially close to the sugar-binding pocket of human rotaviruses (15), it may be speculated that residue 106 may be involved in rotavirus binding of the cell receptor. (16). In our study, such a great genetic discordance between stool and blood strains was not observed, because when typeable, only limited nucleotide divergences were documented.…”
Section: Discussioncontrasting
confidence: 63%
“…Because this region of VP8 is spatially close to the sugar-binding pocket of human rotaviruses (15), it may be speculated that residue 106 may be involved in rotavirus binding of the cell receptor. (16). In our study, such a great genetic discordance between stool and blood strains was not observed, because when typeable, only limited nucleotide divergences were documented.…”
Section: Discussioncontrasting
confidence: 63%
“…Similarly, Ficher et al (2005) 3found that children with primary rotavirus infection, indicated by low titres of rotavirus antibodies in acute phase serum samples, had more antigen detected in their serum than did children with higher acute phase titres, which suggested past infection or the presence of maternal antibodies. Also, in accordance with the same study ofChitambar SD et al (2008) 14 , we noted that serum viremia was detected despite the lower level of antibodies, and the mean IgM level was significantly lower in PCR positive patient as compared to PCR negative patients.…”
supporting
confidence: 93%
“…Of these, three showed gene concordance, whereas two of the five were discordant. This suggests an extraintestinal site of rotavirus infection or differential rotavirus dissemination [10 ]. These findings are similar to those of a recent Italian study [11].…”
Section: Rotavirus (Reovirus)supporting
confidence: 71%